Equity and Inclusion in Assessing Hereditary Cancer Risk: Insights From Excluded Communities, Structured Interviews, and Population Genetics - Janis Geary PhD; Lynette Hammond Gerido PhD, MPH; Amanda M. Gutierrez MPH; Kali J. Dale (Cancer Control)
Including underrepresented population groups in databases and initiatives integral to assessing hereditary cancer risk presents several challenges. Data and knowledge from genome-wide association studies (GWASs) and clinical genomics are based largely on people with predominantly European ancestry. Individuals who do not have this ancestry are under-represented in resources used to make clinical assessments. They are therefore more likely to receive results of “variant of unknown significance” (VUS) from genetic testing. Efforts to broaden representation of population groups have created additional challenges in grouping those with mixed ancestry. Further, the focus on genetics can lead to downplaying the impacts of racism. We describe challenges that must be overcome to include underrepresented population groups, including our insights from our ongoing work within each of 3 population groups that focus on: health care access for heterogeneous Hispanic/Latino populations, engagement with Black, African, and African Diasporic  communities, and Indigenous Data sovereignty. Using empirical data derived from population databases, we demonstrate gaps in hereditary cancer gene variant representation. Our interviews with experts in genetic testing and data sharing suggest ways to create inclusive hereditary cancer data resources. The interview data highlight the inequities that have led to underrepresentation, ranging from patient access to research and health services (especially those that are culturally-sensitive), to funding available for professional training and grants to those who belong to underrepresented groups. Our goal is to ensure the realities of how different excluded groups experience genetic testing are not overlooked in the development of policy to address the broad challenge of hereditary cancer gene variant data sharing. There is no one simple solution to making more inclusive hereditary cancer data resources, but there are many opportunities to improve them and better serve these populations.